The maintenance of chromosome structure: positioning and functioning of SMC complexes. - Jeppsson, K.; Kanno, T.; Shirahige, K.; Sjogren, C. (Nature Reviews. Molecular Cell Biology, 2014)
Structural maintenance of chromosomes (SMC) complexes, which in eukaryotic cells include cohesin, condensin and the Smc5/6 complex, are central regulators of chromosome dynamics and control sister chromatid cohesion, chromosome condensation, DNA replication, DNA repair and transcription. Even though the molecular mechanisms that lead to this large range of functions are still unclear, it has been established that the complexes execute their functions through their association with chromosomal DNA. A large set of data also indicates that SMC complexes work as intermolecular and intramolecular linkers of DNA. When combining these insights with results from ongoing analyses of their chromosomal binding, and how this interaction influences the structure and dynamics of chromosomes, a picture of how SMC complexes carry out their many functions starts to emerge.